1992
DOI: 10.1073/pnas.89.6.2350
|View full text |Cite
|
Sign up to set email alerts
|

Strong evolutionary conservation of neuropeptide Y: sequences of chicken, goldfish, and Torpedo marmorata DNA clones.

Abstract: Neuropeptide Y (NPY) is an abundant and widespread neuropeptide in the nervous system of mammals. NPY belongs to a family of 36-amino acid peptides that also includes pancreatic polypeptide and the endocrine gut peptide YY as well as the fish pancreatic peptide Y. To study the evolution of this peptide family, we have isolated clones encoding NPY from central nervous system cDNA libraries of chicken, goldfish, and the ray Torpedo marmorata, as well as from a chicken genomic library. The predicted chicken NPY a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(89 citation statements)
references
References 30 publications
3
85
0
1
Order By: Relevance
“…Compared with other amphibian sequences, the predicted axolotl NPY sequence displays variation in positions 6 and 7. Although the substitution of Asn for Ser at position 7 has been observed previously in the chicken (Blomqvist et al, 1992), replacement of Asp for Asn at position 6 is unique among reported tetrapod NPY sequences. Within previously known tetrapod NPYs, only four positions have been shown to vary (positions 7, 10, 17, and 19), and 32 positions, particularly those toward the C terminus, remain perfectly conserved (Larhammar, 1996;Cerda-Reverter and Larhammar, 2000).…”
Section: Discussionmentioning
confidence: 82%
“…Compared with other amphibian sequences, the predicted axolotl NPY sequence displays variation in positions 6 and 7. Although the substitution of Asn for Ser at position 7 has been observed previously in the chicken (Blomqvist et al, 1992), replacement of Asp for Asn at position 6 is unique among reported tetrapod NPY sequences. Within previously known tetrapod NPYs, only four positions have been shown to vary (positions 7, 10, 17, and 19), and 32 positions, particularly those toward the C terminus, remain perfectly conserved (Larhammar, 1996;Cerda-Reverter and Larhammar, 2000).…”
Section: Discussionmentioning
confidence: 82%
“…Sequence alignment of amino acids showed that the NPY mature peptide of GIFT tilapia is the identity of that red tilapia (GenBank: AAV49168) and highly homologous to human NPY with the identity of 86%. This result again clearly proved that NPY is the most highly conserved neuropeptide in vertebrates (Blomqvist et al, 1992). In the study of protein function, E. coli is commonly used to express large quantities of protein.…”
Section: Discussionmentioning
confidence: 72%
“…NPY executes these functions mainly through its receptor Y1, Y2 and Y5 (Aldegunde and Mancebo, 2006;Pedrazzini et al, 2003). NPY is one of the most highly conserved neuroendocrine peptides in vertebrates (Blomqvist et al, 1992). The NPY peptides of fish species also showed remarkable sequence homology with mammals, suggesting the similar functions of NPY in fish and mammals (CerdaReverter et al, 2000b;Sundstrom et al, 2005).As its mammalian counterpart, NPY is also a very important regulator of food intake and energy metabolism in fish (Volkoff, 2006;Volkoff et al, 2005).…”
mentioning
confidence: 99%
“…This study has described the first isolation and structural characterization of a PYY-related peptide from a bird, chicken, and complements earlier studies describing the characterization of chicken PP [10] and the cloning and nucleotide sequence analysis of the eDNA encoding chicken NPY [11]. As shown in Table I, evolutionary pressure to conserve the amino acid sequence of the chicken PP-family peptides has been weak, with only 13 invariant residues between the three molecules.…”
Section: Discussionmentioning
confidence: 74%